2018
DOI: 10.1021/acs.macromol.8b00348
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Metal-Free Atom Transfer Radical Polymerization: Experiments and Model-Based Approach for Mechanistic Understanding

Abstract: Metal-free atom transfer radical polymerization (ATRP) was successfully achieved in aqueous media for the first time. Polymerization of poly(ethylene oxide) methyl ether acrylate (PEGA 480 ) was well controlled (Đ < 1.40) under visible light irradiation using tetrabromofluorescein (Eosin Y) as catalyst and pentamethyldiethylenetriamine (PMDETA) as electron donor. A validated kinetic model was developed to investigate the process of photoredox catalytic cycle via reductive quenching pathway. Experimental and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 69 publications
1
67
0
5
Order By: Relevance
“…Bian et al. ′s mechanistic study revealed the importance of the sacrificial electron donor in the reductive quenching mechanism [72] . It was found that the rate of polymerization increases with an increase in the concentrations of electron donors, which results in a higher concentration of the alkyl radicals (P n °), which initiate the polymerization.…”
Section: Organic Photocatalystsmentioning
confidence: 99%
“…Bian et al. ′s mechanistic study revealed the importance of the sacrificial electron donor in the reductive quenching mechanism [72] . It was found that the rate of polymerization increases with an increase in the concentrations of electron donors, which results in a higher concentration of the alkyl radicals (P n °), which initiate the polymerization.…”
Section: Organic Photocatalystsmentioning
confidence: 99%
“…In addition, metal-free ATRP is a very recent technique, with only a few simulation studies that can be cited. [33,41] To the best of our knowledge, no research has Table 1. Reaction mechanism with the fundamental reactions of the metal-free ATRP process.…”
Section: Determination Of Kinetic Parametersmentioning
confidence: 99%
“…Light-driven reactions are vital for all life. [26] To the best of our knowledge,p hotoATRP as as trategy to achievea mplified detection of biomolecules has been rarely reported. [14][15][16][17][18] Recently,p hotoredox catalysts has been widely investigated due to the strongo xidation and reductiono fi ts exciteds tate and poor oxidation and reduction in the grounds tate.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐free photoATRP possesses two photoredox catalytic cycles by means of single electron transfer, oxidative quenching pathway and reductive quenching pathway . Compared with oxidative quenching pathway, the formation of excited states of photoredox catalysts need lower energy in the reductive quenching pathway . To the best of our knowledge, photoATRP as a strategy to achieve amplified detection of biomolecules has been rarely reported…”
Section: Introductionmentioning
confidence: 99%